Non-Destructive Evaluation of Thermal Treatment Influence on Elastic Engineering Parameters of Poplar - Tuğba Yılmaz Aydın; Murat Aydın (Drvna Industrija)
Twelve elastic constants (Young’s modulus (EL, ER, and ET,), shear modulus (GLR, GLT, and GRT) and Poisson’s ratios (νLR, νLT, νRT, νTR, νRL, and νTL)) of Populus canadensis M. were determined by ultrasonic testing and evaluation, and the effect of thermal treatment on these constants was figured out. Samples were modified at 110, 160, and 210 °C for 3 and 6 h. The 2.25 MHz pressure and 1 MHz shear waves were propagated to calculate ultrasonic wave velocities, which were used to dynamically predict the constants. The control values for EL, ER, ET, GLR, GLT, GRT, νLR, νLT, νRT, νTR, νRL, and νTL were 4361 MPa, 1438 MPa, 476 MPa, 771 MPa, 480 MPa, 107 MPa, 0.795, 0.296, 0.863, 0.335, 0.19, and 0.027, respectively. Yet, no data for full elastic constants were reported, and some remarkable differences were observed for moduli and Poisson ratios when compared to other poplar species. Elasticity and shear moduli reached their highest at 160 °C 3h and 110 °C 3h conditions, respectively. The common point of the treatment on moduli was that intense application caused the highest adverse effect, particularly for ET and GRT. Contrary to moduli, apart from νRT and νTR, the lowest values for Poisson’s ratios were not obtained at the intense application. In general, none of the properties presented linear-like advancement or worsening by the increase in treatment conditions. Furthermore, not all the properties were significantly influenced by the treatment. Therefore, defining an optimum thermal treatment condition for improving the wood elastic constants is not easy when considering that the response to thermal treatment changes not only between the species but also within the species. Anyhow, preventing extended duration to elevated temperatures provides considerable advances.